ChemInform Abstract: Catalytic Methods for Aromatic C—H Amination: An Ideal Strategy for Nitrogen‐Based Functional Molecules. Issue 14 (March 2016) - Jiao, Jiao; Murakami, Kei; Itami, Kenichiro
Abstract: Review: 339 refs.